Wideband Absorption at Low Microwave Frequencies Assisted by Magnetic Squeezing in Metamaterials - Wang, Zhenxu; Wang, Jiafu; Han, Yajuan; Fan, Ya; Fu, Xinmin; Pang, Yongqiang; Yan, Mingbao; Li, Yongfeng; Ma, Hua; Xu, Zhuo; Qu, Shaobo (Frontiers in Physics, 2020)
In this paper, magnetic squeezing effect in metamaterials is explored and applied to achieve wideband absorption in low-frequency microwave bands. To this end, a metamaterial absorber (MA) is proposed, which consists of a square lattice of split ring resonator (SRR) placed on top of a magnetic absorbing material (MAM) layer backed by a conducting ground. In the positive resonance region of SRRs, strong magnetic squeezing effect occurs and more concentrated magnetic field lines are confined within SRRs. This results in significant magnetic field enhancement within the MAM layer, which provides a prerequisite for high-efficiency absorption enhancement at low frequencies. To verify this method, we fabricated a prototype using a 3.0mm thick silicone MAM sheet. Both the simulation and experiment results show that with the assistance of magnetic squeezing in the SRR array, the absorption at lower frequencies is significantly enhanced and is above 90% in 1.25-2.31GHz under normal incidence. Furthermore, the MA exhibits satisfactory stability for different polarization states and incident angles due to the square lattice of the SRR array. This design method may find potential applications in fields such as electromagnetic compatibility, wireless communication and others.